Retail bank interest rate pass-through: new evidence at the euro area level - Gabe de Bondt (European Central Bank (ECB), 2002)
This paper presents an error-correction model of the interest rate pass-through process based on a marginal cost pricing framework including switching and asymmetric information costs. Estimation results for the euro area suggest that the proportion of the pass-through of changes in market interest rates to bank deposit and lending rates within one month is at its highest around 50%. The interest rate pass-through is higher in the long term and notably for bank lending rates close to 100%. Moreover, a cointegration relation exists between retail bank and comparable market interest rates. Robustness checks, consisting of impulse responses based on VAR models and results for a sub-sample starting in January 1999, show qualitatively similar findings. However, the sub-sample results are supportive of a quicker pass-through process since the introduction of the euro.
Keywords: E43; G21; 330; euro area; market interest rates; retail bank interest rates